Determination of obesity, stunting, and nutritional habits in disabled children and adolescents - Nişancı Kılınç, Fatma; Çakır, Biriz; Ekici, Emine Merve; Özenir, Çiler (Progress in Nutrition, 2018)
Objective: This study was conducted to determine obesity, stunting and nutritional habits in children and adolescents with disabilities. Methods: The study was carried out in 612 disabled children and adolescents in a 2-19 age group enrolled in 8 special education practice and rehabilitation institutions in Kırıkkale city center in Turkey. The general characteristics and eating habits of the participants were examined and body mass indexes (BMI) were calculated (n=527) to determine obesity and stunting. Results: Of the participants (n=612), 39.2% were female and 60.8% were male, of whom 39.4% were mentally disabled, 37.1% were physically disabled, 12.3% were mentally and physically disabled, and 11.3% were suffering other types of disabilities (speech disorders, learning disability, etc.). Of the participants (n=527), 18.8% were overweight and 17.8% were obese. The rate of overweight (Male:18.5%, Female:19.2%) and obesity (Male:19.1%, Female:15.9%) was higher in males compared to females (p>0.05). The correlation between BMI classification and disability type, disability level, and income level was not statistically significant (p>0.05). The rate of stunting was 24.5%, which was lower in males compared to females (Male:20.4%, Female:30.8%) (p>0.05). There was no statistically significant difference between height-for-age classifications and the type of disability (p>0.05); however, the difference between disability level and income level was significant (p